DESCRIPTION OF THE LARVAE OF CALENDYMA CHILIENSIS (LAPORTE, 1840) (COLEOPTERA: CLERIDAE: CLERINAE) WITH NOTES ABOUT ITS BIOLOGY (Acta Entomológica Chilena, 2022)
The larvae of Calendyma chiliensis (Laporte, 1840) is described for the first time. Figures of it habit, head, mouthparts and urogomphi are provided. Biological notes are given about feeding habits and life cycle.
Keywords: Coleóptera, Cleridae, Calendyma chiliensis, larval morphology